Mekanisme Penyelesaian Sengketa dalam WTO Dispute Settlement Body (DSB) dan Relevansinya Bagi Indonesia - Tesalonika Amazia Simamora (Media Hukum Indonesia (MHI), 2026)
This study aims to analyze the dispute settlement mechanism of the World Trade Organization (WTO) through its Dispute Settlement Body (DSB) and to examine its legal implications for Indonesia as a member state. The study uses both conceptual and statutory methods in a normative legal approach.Â  Primary, secondary, and tertiary legal texts that were qualitatively examined using a descriptive-analytical method comprise the data sources. The findings reveal that the DSBâ€™s dispute settlement mechanism operates systematically, encompassing consultation, panel formation, appeal to the Appellate Body, and binding decision implementation. For Indonesia, DSB rulings have multifaceted legal implications, including obligations to adjust national regulations, impacts on economic sovereignty, and the need to enhance legal and diplomatic capacity in international trade. The study concludes that the DSB plays a crucial role in maintaining a balance between adherence to international law and the protection of national interests.